SRATEGI PENGEMBANGAN PARIWISATA PERAIRAN BERDASARKAN DAYA DUKUNG KAWASAN DAN KESESUAIAN LAHAN PANTAI WATU KODOK GUNUNGKIDUL - Fandika Agustiyar; Nurazizah Fadhila Abusama (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2022)
Watu Kodok Beach is one of the alternative tourist destinations in Gunungkidul. The problems found on the object of Watu Kodok Beach are that the buildings have not been managed according to spatial regulations, and several buildings were destroyed due to abrasion. This study aims to identify the carrying capacity of the area and the level of land suitability of Watu Kodok Beach and determine the appropriate management direction. This research was conducted in July – August 2021 in the Frog Beach area, Kemadang Village, Gunungkidul Regency. The methods used in this research are survey and mapping, sampling, laboratory analysis for water quality testing, area carrying capacity analysis, and land suitability analysis. The results obtained for the area's carrying capacity (DDK) of 1347 people/day with an area of 33678 m2 and a land suitability index of 83.33% are included in the very suitable classification (S1). Directional plans that can be carried out include rearranging buildings around the beach area, making reef balls, and installing informative media and warning signs for tourists.